2001
DOI: 10.1128/cdli.8.2.349-351.2001
|View full text |Cite
|
Sign up to set email alerts
|

Two Methods for Rapid Serological Diagnosis of Acute Leptospirosis

Abstract: Leptospirosis is a common and underdiagnosed zoonosis. Two rapid assays for serological diagnosis of acute leptospirosis in diagnostic laboratories, the immunoglobulin M (IgM)-dipstick assay and the indirect hemagglutination assay (IHA), were evaluated and compared with standard assays. Sera were examined from 104 patients admitted to a hospital for investigation in a leptospirosis diagnostic protocol. Specimens for serology were taken on days 1 and 4 of the patients' hospital stay. Antibodies were detected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 22 publications
3
61
2
2
Order By: Relevance
“…The test is both complex and tedious for routine use. Many studies have demonstrated Pan Bio ELISA to be more sensitive than MAT for detection of cases early in acute illness [34]. IgM antibodies start appearing during the first week of illness though antibody levels are low or not detectable very early on in the illness.…”
Section: Enzyme Linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…The test is both complex and tedious for routine use. Many studies have demonstrated Pan Bio ELISA to be more sensitive than MAT for detection of cases early in acute illness [34]. IgM antibodies start appearing during the first week of illness though antibody levels are low or not detectable very early on in the illness.…”
Section: Enzyme Linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Assays that focus primarily on detecting IgM binding to crude antigen (Adler et al, 1980; Abbreviations: HRP, horseradish peroxidase; MAT, microscopic agglutination test; NC, nitrocellulose. Gussenhoven et al, 1997;Winslow et al, 1997;Smits et al, 1999;Levett et al, 2001), though more sensitive for serodiagnosis, are subject to variations in specificity. However, the nature of IgM-binding antigen has not been identified in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of this study is to identify the risk factors associated with contracting leptospirosis in four western parishes of Jamaica. 16,17 A symptomatic patient with positive results by either of these methods is considered to have clinical leptospirosis by the Jamaica MOH. Controls were matched (1:n) to cases on neighborhood and age (±10 years).…”
Section: Introductionmentioning
confidence: 99%